Graphene oxide coatings prevent Candida albicans biofilm formation with a controlled release of curcumin-loaded nanocomposites. (15th November 2018) - Palmieri, Valentina; Bugli, Francesca; Cacaci, Margherita; Perini, Giordano; Maio, Flavio De; Delogu, Giovanni; Torelli, Riccardo; Conti, Claudio; Sanguinetti, Maurizio; Spirito, Marco De; Zanoni, Robertino; Papi, Massimiliano
Aim: Fabrication of graphene oxide (GO)-based medical devices coatings that limit adhesion of Candida albicans, a main issue of healthcare-associated infections.Methods: The GO composites noncovalently functionalized with curcumin (CU), a hydrophobic molecule with active antimicrobial action, polyethylene glycol (PEG) that hinders the absorption of biomolecules or a combination of CU and PEG (GO–CU–PEG) were drop-casted on surfaces and antifungal efficacy was assessed.Results: We demonstrate that GO–CU–PEG coatings can reduce fungal adhesion, proliferation and biofilm formation. Furthermore, in an aqueous environment, surfaces release curcumin–PEG nanocomposites that have a minimum inhibitory concentration of 9.25 μg/ml against C. albicans .Conclusion: Prevention of early cell adhesion and creation of a proximal environment unfavorable for growth make these GO-supported biomaterials attractive for innovative medical device manufacturing.